AB0802 A Patients Preference Survey for Osteoporosis Medication on 679 Patients: Monthly Drug Regimen Can be the Best for the Adherence. (10th June 2014) - Kido, A.; Akahane, M.; Hara, R.; Shimizu, T.; Nakano, K.; Kobata, Y.; Fujimura, T.; Shinmyo, N.; Akai, Y.; Fujimoto, T.; Tanaka, Y.
Abstract : Background: Bisphosphonates are the first-line therapy for osteoporosis treatment though the long-term persistence and adherence to bisphosphonates remain low (1-2). This medication noncompliance has serious consequences as it is associated with higher morbidity and mortality (3-6). Objectives: To explore patient preferences for the osteoporosis medication, we performed a cross sectional survey. Methods: A questionnaire for the persistence and adherence was distributed to all patients and the attending doctor, who treated osteoporosis in our university hospital, the university teaching hospitals, and the related clinics. The questionnaire was designed that one form contained information from both patients and the attending doctors. A total of 679 questionnaire out of 765 were completed, and the data were evaluated. The medication noncompliance was assessed, and Cox proportional hazards regression was used to estimate the association between treatment regimens and "forgetting to take a medication". For subgroup analysis between young old (<65 yr) and old (over 65yr) generation, the chi-square test was applied. To evaluate (dis)similarity among factors which affect the forgetting, type IV quantification theory was applied. Results: 556 women and 83 men were enrolled; 30% of the patients were in the 80s and 46% were in the 70s. All patients assumed oral bisphosphonates. 66% of the patients were assuming weekly bisphosphonates, 24.4% were assuming monthly bisphosphonates, and 8.7% were assuming daily bisphosphonates. Interestingly, 42 patients answered to assume daily bisphosphonates while the attending doctor reported to prescribe the daily bisphosphonates to 78 patients. In the multivariate logistic regression model, compared with daily bisphosphonates, weekly bisphosphonates was significantly associated with "forgetting to take a medication" (odds ratio 2.01 [95% CI 1.10-3.65]; P<0.05). In the subgroup analysis, the "forgetting frequency" showed no differences, but the young old generation had a tendency to have difficulty ("hassle") for the medication. A proportion of patients who preferred less frequent dosing regimen was significantly larger in the young old than old generation (P<0.05). Conclusions: Weekly drug regimen was significantly associated with incompliance. Considering that less number of patients answered "hassle" for monthly drug regimen, monthly regimen can be the best for adherence among the three regimens. Less frequent dosing regimen was further required especially in young old generation. References: Imaz et al.Osteoporos Int. 2010;21:1943–1951. Kothawala et al.Mayo Clin Proc. 2007;82:1493–1501. Ryg et al. J Bone Miner Res. 2009;24:1299-307. FitzGerald et al. J Bone Miner Res. 2012;27:1907-15. Gehlbach S et al. J Bone Miner Res. 2012;27:645-53. Cameron et al. J Bone Miner Res. 2010;25:866-72. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1628